Is the decrease of fertility a consequence of the postponement of the Entrance in the labour market? - Santos, José (2018)
As the postponement in the age of entrance into the labour market and the fertility decline in Portugal are a primary concern in Society it is important to understand the patterns associated with this issue. Data from the Portuguese Labour Force Survey (LFS) - data source: National Statistical Institute - from 1998 to 2004 was utilised in order to study the evolution of the entrance age into the labour market and the relationships between entrance age, sex and education level. The multinomial logit model evidenced that being a woman, being younger or having a higher qualification implied a later entrance age into the labour market, while being a man, being older or having lower qualifications were involved in an earlier entrance into the labour market.